Tantangan dan Solusi Administrasi Kesehatan di Era Digital ( Tinjauan Literature Review atas Implementasi Teknologi ) - Fauzi, Muhamad Rizal; Saimi, Saimi; Fathoni, Fathoni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is Challenges and Solutions of Health Administration in the Digital Era (Literature Review Review of Technology Implementation). This type of research is a literature study. Data collection with documentation. Data analysis with SLR. The results of the research Based on the literature review on challenges and solutions in health administration in the digital era, it was found that the implementation of health technology offers great opportunities to improve efficiency and quality of services, but is also faced with various obstacles. The main challenges include limited digital infrastructure, lack of skills of health workers in using technology, and patient data security risks. Proposed solutions include increasing investment in technology infrastructure, ongoing training for health workers, and implementing stricter data security policies. By addressing these challenges, technology can significantly improve the effectiveness of health administration and patient care